The Decline in Moral Behavior in Students and What is The Role of Educators - Laelatul Ulfa Toifi (International Journal of Educational Technology Research, 2023)
This research aims to determine the causes of the factors that influence the decline in morality among Indonesian students. And what efforts should be made to increase the morality of students. And what is the role of educators in this regard. In this study, the writing method in this article is the literature method by collecting various reading sources from articles and journals which are then analyzed and then linked to the issues discussed. Key words: Moral behavior in student